Manipulation of neuraminidase packaging signals and hemagglutinin residues improves the growth of A/Anhui/1/2013 (H7N9) influenza vaccine virus yield in eggs. Issue 10 (7th March 2017) - Barman, Subrata; Krylov, Petr S.; Turner, Jasmine C.; Franks, John; Webster, Robert G.; Husain, Matloob; Webby, Richard J.
Highlights: We examined PR8 HA and NA packaging signals' roles on PR8-based Anhui/1 CVVs' growth. PR8 NA's 5′ and 3′ packaging (P-NA-P) signals improve Anhui/1 CVVs' growth in eggs. Egg-adaptive mutation G218E in Anhui/1 HA produces high-yield CVVs. HA-G218E and chimeric NA (P-NA-P) together further improve CVV growth in eggs. Abstract: In 2013, a novel avian-origin H7N9 influenza A virus causing severe lower respiratory tract disease in humans emerged in China, with continued sporadic cases. An effective vaccine is needed for this virus in case it acquires transmissibility among humans; however, PR8-based A/Anhui/1/2013 (Anhui/1, H7N9), a WHO-recommended H7N9 candidate vaccine virus (CVV) for vaccine production, does not replicate well in chicken eggs, posing an obstacle to egg-based vaccine production. To address this issue, we explored the possibility that PR8's hemagglutinin (HA) and neuraminidase (NA) packaging signals mediate improvement of Anhui/1 CVV yield in eggs. We constructed chimeric HA and NA genes having the coding region of Anhui/1 HA and NA flanked by the 5′ and 3′ packaging signals of PR8's HA and NA, respectively. The growth of CVVs containing the chimeric HA was not affected, but that of those containing the chimeric NA gene grew in embryonated chicken eggs with a more than 2-fold higher titer than that of WT CVV. Upon 6 passages in eggs further yield increase was achieved although this was not associated with any changes in the chimeric NA gene. The HA of the passaged CVV, did, however, exhibit egg-adaptive mutations and one of them (HA-G218E) improved CVV growth in eggs without significantly changing antigenicity. The HA-G218E substitution and a chimeric NA, thus, combine to provide an Anhui/1 CVV with properties more favorable for vaccine manufacture.